Increased CDCA2 Level Was Related to Poor Prognosis in Hepatocellular Carcinoma and Associated With Up-Regulation of Immune Checkpoints - Tang, Mengying; Liao, Mingchu; Ai, Xiaohong; He, Guicheng (Frontiers in Medicine, 2022)
Background. Cell division cycle-associated protein 2 (CDCA2) is a member of cell cycle-related protein. CDCA2 plays a role in regulation to protein phosphatase 1(PP1) γ-dependent DNA damage response (DDR) and H3 phosphorylation. CDCA2 promotes the occurrence and development of several types of cancers by promoting the proliferation of tumor cells. However, the correlation between CDCA2 expression and the clinicopathological characteristics of hepatocellular carcinoma is unknown. Methods. Gene expression information and clinical data were download from TCGA database. The expression of CDCA2 and its correlation to clinical characteristics in hepatocellular carcinoma were analyzed. The expression level of CDCA2 was validated in hepatocellular carcinoma cell lines. The relationship between CDCA2 expression and the survival of hepatocellular carcinoma patients were analyzed by Kaplan-Meier method. The prognostic value of CDCA2 in hepatocellular carcinoma was estimated by Cox regression analysis. The expression difference of CDCA2 between hepatocellular carcinoma and normal tissues and its correlation to survival were verified in independent datasets. Gene set enrichment analysis (GSEA) was used to screen the CDCA2-related signaling pathways. Results. CDCA2 expression was upregulated in hepatocellular carcinoma tissues (p<0.001) and increased CDCA2 was correlated to elevated T stage, pathologic stage, histologic grade and AFP level (p<0.001). CDCA2 was also overexpression in hepatocellular carcinoma cell lines HepG2 and LM3. Patients with high CDCA2 expression level had poor overall survival (HR=1.69; 95%CI, 1.20-1.40, p=0.003), disease specific survival (HR=1.73; 95%CI, 1.11-2.71, p=0.016) and progress free interval (HR=1.74; 95%CI, 1.30-2.34, p<0.001). Overexpression of CDCA2 and its relation to poor survival in hepatocellular carcinoma was verified in GEO datasets and Kaplan-Meier Plotter database. GSEA showed that homologous recombination pathway, insulin signaling pathway, MAPK pathway, mismatch repair pathway, mTOR pathway, Notch pathway, T cell receptor pathway, Toll like receptor pathway and WNT pathway were enriched in CDCA2 high expression phenotype. Conclusion: CDCA2 was related topoor prognosis in hepatocellular carcinoma and increased CDCA2 expression was associated with up-regulation of immune checkpoints.